Prevailing circumstances governing abortion in Africa - Unnithan, Vishnu B.; Shree S., Lalitha Lavanya; O. Uzoka, Favour; Shrinivas, Divya; Singh, Shivangi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
A woman's worth is closely tied to childbirth in many African societies. The immense cultural emphasis that is placed on pregnancy means that women are also subject to stigmatization in the event of unintended pregnancies. In the patriarchal societies that commonly make up the region, a woman’s bodily autonomy is often subjugated to insensitive decisions taken by men based on social circumstances. Abortion remains a largely taboo topic with the resulting lack of informed awareness putting women at risk. The current review aims to change that discourse by examining the sociodemographic considerations, beliefs, and traditions across various regions that prevent the effective utilization of existing facilities. The risk factors that govern elective abortions are examined with attention being given to commonly found age-disparate relationships as well as vulnerable and marginalized sections of society. The impact of the pandemic is also discussed with recommendations on multi-level action plans that would allow for effective advocacy. There is a lack of access to safe abortion infrastructure. Strengthening healthcare delivery infrastructure will mitigate the national economic burden and ensure that female reproductive health receives the attention it deserves.